COULD DODECANOIC ACID VCO FROM TRADITIONAL ACEH YEAST FERMENTATION USED AS ANTIVIRAL AGENTS AGAINST 2019-NCOV ? - Annisa Ammalia Kiti; Zairin Thomy; Essy Harnelly (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2021)
Numerous previous studies have proven the efficacy of dodecanoic acid contained by VCO as an antimicrobial, especially antiviral. The global urgency of COVID-19 treatment caused by the 2019-nCoV virus has prompted many researchers around the world to seek effective drugs to cure this infectious disease. Based on the claim that dodecanoic acid and its derivatives can be used as an antiviral, this study aims to determine the levels of VCO dodecanoic acid produced from the traditional yeast fermentation of Aceh, Indonesia. The making of VCO through fermentation with the addition of starter yeast as much as 10% in coconut milk. Analysis of dodecanoic acid levels was performed using Gas Chromatography-Mass Spectroscopy (GC-MS). The results showed that the composition of dodecanoic acid in VCO-pe was higher than VCO-ti. VCO-pe contains about 44.23% dodecanoic acid, while VCO-ti contains about 43.63% dodecanoic acid. The composition of dodecanoic acid contained in VCO-pe was higher than VCO-ti. The composition of dodecanoic acid in VCO has met APCC standards, namely 43.0% -53.0%. These results could append new information about the application of dodecanoic acid in VCO as an antiviral candidate against 2019-nCoV which causes the COVID-19 outbreak.Keywords: antimicrobial, coronavirus, COVID-19, levels of lauric acid, virgin coconut oil